The presence of placeholders modulates the naso-temporal asymmetry in the remote distractor effect. (August 2021) - Casteau, Soazig; Lodge, Rebecca; Chalkley, Mary; Walker, Robin; Smith, Daniel T.
Abstract: The remote distractor effect (RDE) is a well-known and robust phenomenon whereby latencies of saccades are increased when a distractor is presented simultaneously along with the saccade target. Studies of the RDE in patients with a loss of vision in one visual field (hemianopia) following damage to primary visual cortex have provided conflicting results. Rafal, Smith, Krantz, Cohen, and Brennan (1990) reported a naso-temporal asymmetry in the RDE in patients with hemianopias, with a greater influence of distractors presented in their blind temporal visual field. This asymmetry was not observed in typically sighted controls. By contrast, Walker, Mannan, Maurer, Pambakian, and Kennard (2000) observed no effect of distractors presented to either the blind nasal or blind temporal hemifield of hemianopes, but the naso-temporal asymmetry was observed in typically sighted controls. The present study addressed one potential methodological differences between the two studies by investigating the inhibitory effect of a distractor on saccade latency in neurotypical participants. Here participants were tested monocularly and the effect of a nasal/temporal hemifield distractor on saccade latency observed in the presence or absence of peripheral placeholders. Our results showed a naso-temporal asymmetry in the magnitude of the RDE in the no placeholder condition, with a greater RDE when the distractor was presented in the temporal visual field. However, in the placeholder condition the opposite asymmetry was observed, that is an increased RDE when the distractor was presented in the nasal visual field. Our results suggest that the presence/absence of a placeholder might be the critical factor explaining the discrepancy between Rafal et al. (1990) and Walker et al. (2000) in participants without visual field loss. The current results can be interpreted in terms of additional inhibitory or attentional processes that bias selection towards stimuli in the nasal hemifield in the presence of placeholders, still, the mechanisms underlying these effects remain unclear.